Effect of using a mobile drug management application on medication adherence and hospital readmission among elderly patients with polypharmacy: a randomized controlled trial - Hossein Poorcheraghi; Reza Negarandeh; Shahzad Pashaeypoor; Javad Jorian (BMC, 2023)
Abstract Background Adherence to complex drug regimens and polypharmacy are among the challenges of old age, which may negatively affect their motivation to continue drug therapy or lead to incorrect drug consumption. The present study was conducted to evaluate the effect of using a mobile drug management application on medication adherence and hospital readmission among polypharmacy older adults. Methods In this randomized controlled trial study conducted in 2022, with Trial Registration Number (IRCT20191231045966N1) (18/07/2021), 192 Iranian older adults with polypharmacy were selected according to the inclusion criteria and allocated to case and control groups using the block randomization method. The data collection tools included a demographic questionnaire, case report form, and Morisky Medication Adherence Scale. The intervention was done using a mobile drug management application. Drug adherence was measured at baseline and both with hospital readmission were measured after 8 weeks. The collected data were entered into the SPSS software version 22 and analyzed using descriptive (frequency, percentage, mean, standard deviation) and inferential (Chi-square, Fisher's exact test, independent t-test) statistics. Results The case and control groups were homogeneous in terms of demographic variables and drug adherence level before the intervention. A significant difference was found in the drug adherence level after using the app (p < 0.001). Moreover, a significant difference was found in adverse events, including re-hospitalization due to disease aggravation, re-hospitalization due to error in medication consumption, falling, hypo or hypertension, and hypo or hyperglycemia, and medication use accuracy between the groups after the intervention (p < 0.05). Conclusion The results showed that using a mobile drug management application that meets the specifications of older adults can improve drug adherence, reduce the adverse events and pave the way for a better disease period management.